DESCRIPTION OF URIC ACID LEVELS BUS DRIVER PT ARSA BUANA MANUNGGAL KARANGASEM - Yulia, Ni Putu Mentari; oka suyasa, ida bagus; sudarmanto, i gede; suyasa, i nyoman gede (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Uric acid is the end result of breaking down a substance called purine. Purine substance is a natural substance which one of the chemical structure groups is the formation of DNA and RNA. Uric acid can be influenced by several factors such as age, long sitting while driving, consumption of alcoholic beverages, and consumption of foods high in purines. The aim of this study was to determine uric acid levels in PT.ABM drivers. The study sample consisted of 45 people selected by random sampling using the POCT method with the Autoclick Easy Touch GCU tool. The results showed normal uric acid levels in 32 people (71.1%) and high uric acid levels in 13 people (28.9%). High uric acid levels were more common at the age of 43-51 years in 5 people (45.5%), duration of sitting while driving was dominated by driving duration for ? 7 hours/day in 10 people (29.4%), while drivers 11 people (34.4%) consumed alcoholic beverages and 25 people (55.6%) consumed high-purine foods. The conclusion of this study is that high uric acid levels occur in respondents aged 43-51 years, driving for ? 7 hours/day, consuming alcoholic beverages and consuming foods high in purines.